The Impact of Green Human Resource Management Practices on Employee Performance: The Mediating Role of Job Satisfaction Among Employees at PT POS Indonesia Surakarta Branch - Andhea Pramesti; Jati Waskito (Universitas KH. Abdul Chalim Mojokerto, 2025)
Green Human Resource Management (GHRM) or human resource management in the context of sustainability can help an organization create a comfortable, productive, and ethical workplace. The purpose of this study is to analyze the impact of GHRM practices on employee performance, with job satisfaction acting as a mediator. This research employs a quantitative method with an expanded sample size of 150 respondents, including employees from multiple branches of PT Pos Indonesia to enhance generalizability. Data was collected by distributing questionnaires randomly to employees across different branches. The data analysis method used in this study is Partial Least Squares (PLS) with SmartPLS version 3 software. The findings of this study show that GHRM practices have a significant positive effect on job satisfaction. Similarly, job satisfaction has a significant positive effect on employee performance. Job satisfaction fully mediates the effect of GHRM practices on employee performance. Additionally, control variables such as job type, organizational culture, and individual personality traits were considered to ensure a more comprehensive analysis of factors influencing the relationship between GHRM practices, job satisfaction, and employee performance. The results of this study provide practical implications for PT Pos Indonesia, emphasizing the importance of implementing GHRM practices as a core part of their business strategy to enhance job satisfaction and employee performance across different branches and organizational contexts.